M.o.m.: mother of madness ebook - Clarke, Emilia (M.O.M.: Mother of Madness (2021)., 2021)
The mayhem begins with Maya, under-the-weather scientist by day, over-the-top superhero by night, and badass single mom 24/7. Deadpool action and Fleabag comedy collide when Maya activates her freakish superpowers to take on a secret sect of human traffickers. Bath time's at seven, bedtime's at eight, and crime-fighting never sleeps when villains from Maya's shadowy past come to collect.